2015
DOI: 10.5125/jkaoms.2015.41.5.273
|View full text |Cite
|
Sign up to set email alerts
|

Primary oral soft tissue angiosarcoma of the cheek: a case report and literature review

Abstract: Angiosarcoma is a rare and aggressive malignant tumor that has a poor prognosis. It represents less than 1% of all malignancies occurring in the oral cavity and salivary glands. We present a 35-year-old male with angiosarcoma of the cheek following traumatic injury and a review of the current literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 8 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…Of the cases included in this review, 11 reported a predominant or partially spindled morphology [17,18,25,27,31,29,34]. For tumours showing a spindled phenotype, spindle cell carcinoma must be considered in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the cases included in this review, 11 reported a predominant or partially spindled morphology [17,18,25,27,31,29,34]. For tumours showing a spindled phenotype, spindle cell carcinoma must be considered in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when site of occurrence is considered, 43% (3/7) of patients with angiosarcoma in the tongue died of disease (DOD) [4,18], 64% (7/11) cases from the gingiva DOD [17,18,21,24,26,32,33], and no cases from the buccal mucosa or lip died of disease [4,22,25,29]. It should be noted; however, in two cases involving the cheek/buccal mucosa area, the duration of follow-up was extremely short [25,29]. Due to the limited number of cases published, definitive conclusions about the biological behaviour of primary oral angiosarcomas cannot be made, particularly with respect to how behavior may differ from cutaneous angiosarcomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas of organized thrombus in the dilated vessels and proliferation of endothelial cells in papillary form toward the lumen are important for diagnosis of IPEH. The circumscribed and intravascular location of the lesion and presence of thrombotic material, along with absence of nuclear hyperchromia, cellular pleomorphism, atypical mitosis, foci of necrosis, and irregular capillary vessels are also major features differentiating IPEH from angiosarcoma16.…”
Section: Discussionmentioning
confidence: 99%
“…Angiosarcoma is an extremely rare malignant mesenchymal tumor of vascular or lymphatic origin 1 . This type of tumor represent less than 1% of all malignant tumors, and about 50% of angiosarcomas are found in the head and neck region, with only approximately 1% reported to occur in the oral cavity or salivary glands 1,2 . Angiosarcoma most commonly affects the elderly and is predominant in males, with a male to female ratio of 2:1 3 .…”
Section: Introductionmentioning
confidence: 99%